Development of Konseling-Ku.id website to improve Islamic guidance and counseling services - Widyarto, Wikan Galuh; Pohan, Rizky Andana; Soleha, Irfana (ENLIGHTEN: Jurnal Bimbingan Konseling Islam, 2024)
In the current era of the industrial revolution 4.0, digital technology-based innovations are urgently needed and are growing rapidly. The development method in this study is the Borg and Gall development model. The researcher made a development in the form of a website media named "konseling-ku.id". The purpose of research and development is to produce "Website Development "konseling-ku.id" to improve Islamic counseling guidance services. Based on the analysis of data from the development research results regarding konseling-ku.id websites in avery clear category, based on an assessment of usefulness, convenience, accuracy, attractiveness, and clarity that have been validated by two expert validators. The results of the qualitative analysis data are used as input to revise the product until the final product is produced on the konseling-ku.id website to improve the Islamic guidance and counseling services that have been theoretically accepted. The results of research and development show the effectiveness of counseling services through the https://konseling-ku.id/ website because it can provide convenience and benefits for peer counselors, professional counselors and counselors to conduct counseling that is not limited by distance and time.